Influence of transglutaminase treatment on the physicochemical, rheological, and melting properties of ice cream prepared from goat milk - Hatice Şanlidere Aloğlu; Yılmaz Özcan; Salih Karasu; Bayram Çetin; Osman Sağdiç (Mljekarstvo, 2018)
This study was conducted to evaluate the effects of the transglutaminase enzyme on the physicochemical characteristics, overrun, melting resistance, rheological and sensorial properties of ice cream made from goat’s milk. Different enzyme units (0.5, 1, 2, and 4 U/g milk protein) and treatment times (20 min and 60 min) were applied to determine the optimum process conditions. Treatment of the transglutaminase in the ice cream mix significantly affected the rheological and melting properties of the ice cream samples. The samples prepared with higher enzyme units and enzyme-treatment times showed higher melting resistance, consistency index, and viscoelastic modulus (G’) than the ice cream mix. The correlation coefficient between melting resistance and viscoelastic modulus was found to be high (0.76). The apparent viscosity of all samples decreased with increasing the shear rate, indicating that all samples exhibited non-Newtonian shear thinning flow behavior. The sensory, overrun, and physicochemical properties of samples were not affected by the enzyme treatment. This study showed that treatment times and enzyme units are essential factors in the processing of the transglutaminase enzyme for improving the rheological and melting properties of ice cream mixes. Another significant result was that desired melting resistance could be achieved for ice cream with lower stabilizer and fat content.